Vegetation succession over an area of a medieval ecological disaster. The case of the Bledów Desert, Poland - Rahmonov, Oimahmad; Oles, Wojciech (ERDKUNDE, 2010)
The Bledów Desert in the southern part of Poland is an extensive area of sands and gravels. The origin of the desert had nothing to do with climatic conditions: The effective cause was the development of a major mining and metallurgical industry that started in the 13th century. The surrounding forests were the main fuel source for the industry. In second half of the 20th century, the ca. 18 sq km desert was one of the largest inland areas of blown sand in Central Europe. Based on the analysis of maps from 1804, 1911, 1914 and 1933 and of aerial photographs taken in 1955, 1973 and 1996, changes in the landscape of the B³êdów Desert area and in the outline of permanent and drift sands were estimated, as was the gradual overgrowth of the area. The study shows that over ca. 200 years, the vegetation succession in the desert occurred in primary and secondary ways and that it can be divided into 9 phases that are grouped into 3 stages. The primary succession took place in areas covered by loose, bare sand, the secondary succession in areas with remnants of fossil soils. The essential ecological and environmental importance of an initial phase involving algae and cyanobacteria was investigated. This involvement facilitated colonisation by species with high ecological requirements through the fixing of loose sands, moisture absorption and the retention and improvement in edaphic conditions. Up to now, such a phase has not been described in terms of species composition and habitat, but this was done in this study.